EFFECT OF MONENSIN ENRICHED MULTI NUTRIENT BLOCK SUPPLEMENTATION ON PERFORMANCE OF LACTATING MURRAH BUFFALOES - Yadav, Dinesh; Nayak, Sunil; Khare, Ankur; Sharma, Rahul; Keshri, Anchal; Muwel, Nirmala; Sharma, Pramod (Buffalo Bulletin, 2025)
Present study was conducted to determine the effect of monensin enriched multi nutrient block supplementation on performance of lactating Murrah buffaloes. Eighteen lactating Murrah buffaloes were divided into three experimental groups (T1, T2 and T3) having six animals in each group on the basis of average body weight (552.72±4.78 kg), average milk yield (8.25±0.10) and stage of lactation (13 weeks post-partum). Experimental buffaloes were fed total mixed basal diet, comprising of wheat straw and concentrate (51.28:48.72; roughage: concentrate mixture) to fulfil the nutrient requirement according to ICAR (2013) feeding standard. Animal of Group T1 were supplemented with basal diet, T2 supplemented with TMR (84% TMR of T1) + multi nutrient block (MB) and wheat straw (ad libitum) and T3 supplemented with TMR (84% TMR of T1) + monensin enriched multi nutrient block (MMB) and wheat straw (ad libitum). The results showed that supplementation of monensin enriched multi nutrient block had no effect on total dry matter intake, feed conversion efficiency, body condition score (BCS), persistency of milk production and milk composition. Milk yield was increase significantly from 8th week to 13th week in MMB Supplemented group (T3) and MB Supplemented group (T2) as compared to Control group (T1). Gradual reduction in milk yield was observed in all the Treatment groups which was 28%, 24%, 21% in Control, MB Supplemented (T2) and MMB Supplemented group (T3), respectively. Results of the present study suggested that dietary supplementation of monensin enriched multi nutrient block is beneficial.